High-yield preparation of new crown ether-based cryptands and improving complexation with paraquat, paraquat derivatives and diquat. Issue 49 (8th December 2016) - Xu, Zhikai; Chen, Mujuan; Liang, Jidong; Zhang, Suhui; Guo, Manli; Li, Ying; Jiang, Lasheng
Abstract: Efficient syntheses of two novel cryptands2a and2b based on bis( m -phenylene)-32-crown-10 are reported. Unimolecular macrocyclization of9 through copper(II)-mediated Eglinton coupling generated the diacetylene-containing cryptand2a in 93% yield. Pd/C-catalyzed hydrogenation of2a yielded the cryptand2b (74%). The complexation behavior of a series of cryptand hosts (1a –2b ) with dicationic guests (3 –6 ) has been comprehensively investigated by NMR spectroscopy, mass spectrometry and X-ray analysis. It is found that all four cryptands binding with guests form 1:1 complexes both in solution and in the solid state, except the case of cryptand1a /1b with5 forming 2:1 complex. Moreover, it is demonstrated that cryptand2a /2b not only binds guests more strongly than the corresponding BMP32C10, but also has greater interacting affinities than the cryptand1a /1b . Meanwhile, the association constants of the N -methyl-substituted guests4 and5 with cryptands are higher than non-methyl-substituted guest3 . The X-ray analysis of crystals of these complexes revealed that the complexation is stabilized by π–π stacking interactions and CH⋯O hydrogen bonds between the cryptands and the guests. Additionally, the paraquat derivative3 penetrated symmetrically through the cavity of the two same 29-membered rings of cryptand2 in the solid state, while the threading of paraquat unit into the cavity of cryptand1 was unsymmetrical both in crystal structures of1a 3 and1b 3 . Graphical abstract: